Paradigm of emerging floriculture and landscape industry for elegancy - Malhotra, S K (Indian Horticulture, 2024)
Floriculture has made appreciable growth in the last three decades as commercial venture. Floriculture production in India covers 285,000 hectares with a production of 2,284,000 tonnes loose flowers and 947,000 tonnes cut flowers every year (2023-24). There is transformation in business to landscape design, contracting and maintenance services, wholesale and retail sales, development of parks and leisure places, gardens, greenhouses including various greenhouse inputs besides providing technical advices. Our country has exported 19,677.89 MT of floriculture products worth ₹ 717.83 Crores/ 86.63 Million USD in 2023-24 to the world. The USA, the Netherlands, United Arab Emirates, UK, Canada and Malaysia were major importing countries of Indian floriculture produce. New distribution structure with the aid of IT is likely to be in place, which would be emphasizing a hitech production system, virtual market, branding, cataloguing and quality assurance.